Persepesi Guru Terhadap Penerapan Merdeka Belajar Melalui Model Pembelajaran Blanded Learning Pada SMA Negeri 12 Buru - Loilatu, Siti Hajar; Mukadar, Suraya; Badu, Tri Kurnia; Hentihu, Vivi Rahim; Kasmawati (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
This research aims to find out teachers' perceptions of the application of independent learning through a blended learning learning and what factors are obstacles in the application of independent learning through blended learning model at SMA Negeri 12 Buru. The research method of this research is descriptive types and approaches of qualitative research. The results of the study can be concluded as follows: Teachers' perceptions of the application of independent learning through a blended learning model at SMA Negeri 12 Buru, namely the application of independent learning at SMA Negeri 12 Buru has not been running or implemented because independent learning has not been socialized in schools directly to provide an understanding of independent learning to all elements of the school, both teachers, educational personnel, and students. During the Covid-19 pandemic, learning was carried out offline and online, namely online learning for students who have android-based cellphones while students who do not have android-based cellphones learn offline, namely teachers visit students in their respective homes the blended learning model during the Covid-19 pandemic helped the implementation of the learning process at SMA Negeri 12 Buru. Factors that become obstacles in the application of independent learning through a blended learning model at SMA Negeri 12 Buru are: 1) Limited learning facilities and infrastructure, 2) Schools do not have human resources for educational personnel, 3) Limited internet quotas, 4) Limited internet network access, 5) Lack of teacher ability to use information technology, 6) Economic limitations of parents.